Factors influencing young entrepreneurs’ investment decision - Leyani, Etika Mery; Hatta, Madani; Marietza, Fenny; Bernoza, Amellia Poetri (Proceeding International Conference on Accounting and Finance, 2024)
The purpose of this research is to determine the effect of financial literacy, financial technology and risk perception on the investment decision behavior of young entrepreneurs by identifying locus of control as a moderating variable. This study used quantitative methods and questionnaire-based data collection techniques. Using purposive sampling techniques, the sample in this study was 100 individuals. SmartPLS 4.0 was used as the analysis technique in this study. The results show that financial literacy, financial technology, and risk perception have significant positive effects on investment decisions. For the moderating variables, locus of control has a significant positive impact on the impact of financial literacy on investment decisions, but locus of control fails to moderate the relationship between financial technology and risk perception on investment decisions.